Alcohol Consumption, Obesity, and Psychological Distress in Farming Communities—An Australian Study. Issue 3 (28th January 2013) - Brumby, Susan; Kennedy, Alison; Chandrasekara, Ananda
Abstract Purpose Alcohol consumption patterns nationally and internationally have been identified as elevated in rural and remote populations. In the general Australian population, 20.5% of adult males and 16.9% of adult females drink at short‐term, high‐risk levels. Farmers are more likely to drink excessively than those living in major cities. This study seeks to explore the relationships between farmers' physical and mental health and their alcohol consumption patterns. Our hypothesis is that farmers consume alcohol at high‐risk levels more often than the Australian average and that this consumption is associated with obesity and psychological distress. Methods Cross‐sectional descriptive data were collected within Australian farming communities from 1, 792 consenting adults in 97 locations across Australia. Data on anthropometric measurements, general physical attributes and biochemical assessments were used to explore the interrelationships of self‐reported alcohol consumption patterns with obesity, psychological distress, and other physical health parameters. Findings There was a higher prevalence of short‐term, high‐risk alcohol consumption (56.9% in men and 27.5% in women) reported in the study compared with national data. There was also a significant positive association between the prevalence of high‐risk alcohol consumption and the prevalence of obesity and abdominal adiposity in psychologically distressed participants. Conclusions The prevalence of short‐term, high‐risk alcohol consumption practices in this cohort of farming men and women is significantly higher than the Australian average. These consumption practices are coupled with a range of other measurable health issues within the farming population, such as obesity, hypertension, psychological distress, and age.